The design and performance of QR-based recognition software for distribution station components - Maryadi, Totok Heru Tri; Priyambudi, Rizal; Badarudin, Rohjai; Martono, Muhhamad Kukuh Budi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
This study aims to determine the design and performance of Recognition Software for Distribution Station Components based on the Quick Response Code (QR-code) for the Flexible Manufacturing System Laboratory Work. This study uses a Research and Development (R&D) method based on Modified Waterfall Model from the Systems Development Life Cycle (SDLC). The development stages consist of Requirements Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, and Operation and Maintenance. The functional suitability test yielded excellent results, scoring 100%. Similarly, the compatibility test achieved a high score of 95%. The interaction capability test also performed well, scoring 85.56%. Additionally, the performance efficiency test showed impressive results, averaging 0.026 seconds per frame with an average of 7% CPU and 279 Mb memory resource utilization. The overall quality and performance of the D-Static application are very suitable for use as a Distributing Station components recognition application based on QR-Code for the Flexible Manufacturing System Laboratory Work.